A MARKETING COMMUNICATION STRATEGY OF DELIVERY SERVICES J&T EXPRESS IN THE DIGITAL MARKETING ERA IN IMPROVING CUSTOMER SERVICE IN MEDAN CITY - Novita Belia Munthe (Jurnal Scientia, 2023)
Currently marketing communications really need to take advantage of technology and the internet which is much more profitable. Opportunities and challenges to carry out internet marketing communications are a new challenge where companies convey messages to their customers with various media. The purpose of this study is to determine the marketing communication strategy for J&T Express shipping services in the digital marketing era in improving customer service in the city of Medan and to find out whether digital marketing can improve customer service. Then facing competition from other delivery services and increasing customer service. J&T Express is unable to compete with other shipping services due to the estimated long delivery time. J&T Express also uses social media communication channels, namely Instagram, so that customers and companies can easily communicate. Instagram social media is used as a medium to promote free shipping promos for J&T Express delivery services. Then facing competition from other delivery services and increasing customer service. J&T Express is unable to compete with other shipping services due to the estimated long delivery time. J&T Express also uses social media communication channels, namely Instagram, so that customers and companies can easily communicate